Emergency Department use of Apneic Oxygenation Versus Usual Care During Rapid Sequence Intubation: A Randomized Controlled Trial (The ENDAO Trial). (23rd September 2017) - Caputo, Nicholas; Azan, Ben; Domingues, Rui; Donner, Lee; Fenig, Mark; Fields, Douglas; Fraser, Robert; Hosford, Karlene; Iuorio, Richard; Kanter, Marc; McCarty, Moira; Parry, Thomas; et al.
Abstract: Objectives: Desaturation leading to hypoxemia may occur during rapid sequence intubation (RSI). Apneic oxygenation (AO) was developed to prevent the occurrence of oxygen desaturation during the apnea period. The purpose of this study was to determine if the application of AO increases the average lowest oxygen saturation during RSI when compared to usual care (UC) in the emergency setting. Methods: A randomized controlled trial was conducted at an academic, urban, Level I trauma center. All patients requiring intubation were included. Exclusion criteria were patients in cardiac or traumatic arrest or if preoxygenation was not performed. An observer, blinded to study outcomes and who was not involved in the procedure, recorded all times, while all saturations were recorded in real time by monitors on a secured server. Two‐hundred patients were allocated to receive AO ( n = 100) or UC ( n = 100) by predetermined randomization in a 1:1 ratio. Results: A total of 206 patients were enrolled. There was no difference in lowest mean oxygen saturation between the two groups (92, 95% confidence interval [CI] = 91 to 93 in AO vs. 93, 95% CI = 92 to 94 in UC; p = 0.11). Conclusion: There was no difference in lowest mean oxygen saturation between the two groups. The application of AO during RSI did not prevent desaturation of patients in this study population.